REKONSTRUKSI PERAN AFEKTIF AYAH DALAM PENDIDIKAN AKHLAK ANAK: STUDI PEMIKIRAN SYAIKH SAID ROMADHON DI KITAB HADZA WALIDZI - Sutikno; Khotimah Suryani; Syihabuddin Qulyubi (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRAK The phenomenon of the fatherless generation and digital disruption has weakened fathers' involvement in family education, thereby affecting children's character and moral development. This condition highlights the need to reconstruct the concept of fatherhood by emphasizing not only the fulfillment of material needs but also the affective, spiritual, and educational dimensions from the perspective of Islamic education. This study aims to analyze the concept of the father's affective role in Islamic education, examine Shaykh Said Ramadhan al-Buthi's thoughts in Hadza Walidzi regarding children's moral development through fathers' affective involvement, and reconstruct these ideas within the context of contemporary child education. This study employed a qualitative approach using library research. The primary data source was Hadza Walidzi, while secondary data were obtained from relevant scholarly publications. Data were analyzed through content analysis using a hermeneutic approach, involving data reduction, categorization, interpretation, and source triangulation. The findings reveal that the father's affective role in Islamic education comprises five essential dimensions: fostering emotional security (tamkin), serving as a wise communicator, being an attentive listener, acting as a consistent role model, and functioning as a moral anchor. Al-Buthi's educational thought emphasizes that children's moral development is nurtured through emotional presence, exemplary conduct, compassionate communication, spiritual guidance, and the gradual development of independence through trust. Furthermore, this study proposes a reconstruction of al-Buthi's thought by promoting affective digital dialogue, progressive role modeling, and more systematic paternal involvement in parenting, thereby offering a conceptual framework for strengthening Islamic family education in the digital era. ABSTRAK Fenomena fatherless generation dan disrupsi digital telah melemahkan keterlibatan ayah dalam pendidikan keluarga sehingga berdampak pada pembentukan karakter dan akhlak anak. Kondisi tersebut menunjukkan perlunya rekonstruksi konsep peran ayah yang tidak hanya berorientasi pada pemenuhan kebutuhan material, tetapi juga menekankan dimensi afektif, spiritual, dan edukatif dalam perspektif pendidikan Islam. Penelitian ini bertujuan untuk menganalisis konsep peran afektif ayah dalam pendidikan Islam, mengkaji pemikiran Syaikh Said Ramadhan al-Buthi dalam kitab Hadza Walidzi mengenai pembentukan akhlak anak melalui keterlibatan afektif ayah, serta merekonstruksi gagasan tersebut dalam konteks pendidikan anak kontemporer. Penelitian menggunakan pendekatan kualitatif dengan jenis penelitian kepustakaan (library research). Data primer bersumber dari kitab Hadza Walidzi, sedangkan data sekunder diperoleh dari berbagai literatur ilmiah yang relevan. Data dianalisis menggunakan teknik content analysis dengan pendekatan hermeneutik melalui proses reduksi, kategorisasi, interpretasi, dan triangulasi sumber. Hasil penelitian menunjukkan bahwa peran afektif ayah dalam pendidikan Islam mencakup lima dimensi utama, yaitu penanam rasa aman (tamkin), komunikator penuh hikmah, pendengar yang baik, teladan yang konsisten, dan moral anchor. Pemikiran al-Buthi menegaskan bahwa pembentukan akhlak berlangsung melalui kehadiran emosional, keteladanan, komunikasi penuh kasih sayang, perlindungan spiritual, serta pemberian kepercayaan kepada anak. Penelitian ini juga menghasilkan rekonstruksi pemikiran al-Buthi melalui penguatan dialog afektif berbasis digital, keteladanan yang progresif, dan keterlibatan ayah yang lebih sistematis dalam pengasuhan, sehingga memberikan kontribusi konseptual bagi penguatan pendidikan keluarga Islam di era digital.